Sales Growth, Net Profit Margin, Return On Equity, dan Cost Of Fund Terhadap Struktur Modal (Studi Kasus pada Perusahaan Otomotif dan Komponen yang Ter-daftar di Bursa Efek Indonesia Tahun 2015-2018) - Susilawati Susilawati (Jurnal Keuangan dan Perbankan, 2018)
The capital structure of companies is substantial for every company because the capital structure of com-panies has a direct effect on the financial position of the company. This research aims to get empirical evi-dence on the influence of financial performance that is represented by sales growth, net profit margin, re-turn on equity and cost of fund to the capital structure. This research takes 12 samples of automotive and component companies which are listed in Indonesia Stock Exchange from 2015-2018. The method used in the research by using multiple linear regression analysis by the research aim on simultaneously and par-tial influence contribution analysis. This study concludes that independent variables sales growth, net profit margin, return on equity and cost of the fund are simultaneously have a positive influence and signif-icant with capital structure. The independent variables that have a positive and significant influence on the capital structure are sales growth, net profit margin and return on equity and cost of fund. However, inde-pendent variables that partial have significance influence to the capital structure is net profit margin. It means that the net profit margin is the best representation of independent variables to appraise that capital structure on automotive and component company .